Ductal lavage: a way of carefully tracing the breast-secreting duct. Issue 3 (May 2006) - Russo, Antonio; Gregorio, Valter; Sisto, Pasqua Sandra; Calòò, Valentina; Agnese, Valentina; Augello, Claudia; Cascio, Sandra; Badalamenti, Giuseppe; Fricano, Salvatore; Napoli, Liborio; Giordano, Antonio; Santini, Daniele; et al.
Background: Breast cancer is the most commonly diagnosed neoplasia in women after nonmelanoma skin tumors. Unfortunately, present-day diagnostic methods are unable to identify the presence of a cancer until it has been developing for several  years. Currently, ductal lavage seems to represent a new method of reaching an early diagnosis of breast cancer.Materials & methods: This study analyzed 30 patients with ages ranging from 40  to 55  years; and in 26 of these patients, we were able to obtain a sufficient quantity of material for cytological and biomolecular analysis.Results & conclusion: We propose an easy, reproducible method that makes it possible to obtain a detailed map of the nipple, in order to re-identify the duct orifice and take a series of repeated samples from it over a period of time. This procedure is a promising screening and translational research tool since it provides the quantity and quality of ductal fluid required for subsequent cytological and biomolecular analyses.